Complex feedbacks among human and natural systems and pheasant hunting in South Dakota, USA - Laingen, Christopher R. (Kansas State University, 2009)
Land-change science has become a foundational element of global environmental change. Understanding how complex coupled human and natural systems (CHANS) affect land change is part of understanding our planet and also helps us determine how to mitigate current and future problems. Upland birds such as the Ring-Necked Pheasant (Phasianus colchicus) have been widely studied. While myriad studies have been done that show relationships between land change driving forces and the pheasant, what are not found are long-term, comprehensive approaches that show the historical importance of how past land change drivers can be used to gain knowledge about what is happening today or what may happen in the future. This research set out to better understand how human and natural driving forces have affected land change, pheasants, and pheasant hunting in South Dakota from the early 1900s to the present. A qualitative historical geography approach was used to assemble information from historic literature and South Dakota Game, Fish, and Parks Department annual reports to show the linkages between human and natural systems and how they affect pheasant populations. A quantitative approach was used to gather information from hunters who participated in the 2006 pheasant hunting season. Two-thousand surveys were mailed that gathered socioeconomic data, information on types of land hunted, thoughts on land accessibility issues, as well as spatial information on where hunters hunted in South Dakota. Results from the hunter surveys provided some significant information. Non-resident and resident hunters tended to hunt in different parts of the state. Non-resident hunters were older, better educated, and had higher incomes than resident hunters. Resident hunters, when asked about issues such as crowded public hunting grounds and accessibility to private lands had more negative responses, whereas non-resident hunters, especially those who hunt on privately-held lands, were more satisfied with their hunting experiences. Linkages were also seen between changes in human and natural systems and pheasant populations. Some of the most important contributors to population changes were large-scale conservation policies (Conservation Reserve Program) and agricultural incentives, as well as broader economic issues such as global energy production and national demands for increases in biofuel production (ethanol and biodiesel). Many of the changes in pheasant populations caused by changes in human systems have been exacerbated by changes in natural systems, such as severe winter weather and less-than-optimal springtime breeding conditions.
Keywords: land change science; South Dakota; ring-necked pheasant; coupled human and natural systems; Geography (0366)